Screening brinjal (Solanum melongena) accessions conserved in the National Genebank collected from states adjoining Bangladesh for adventitious presence of EE1 event - Indaldas, Kuwardadra Sahadeo; Pandey, Chithra Devi; Paliwal, Aparna; Randhawa, Gurinderjit (The Indian Journal of Agricultural Sciences, 2020)
Systematic management of Plant Genetic Resources (PGRs) is the key to sustainable agriculture for food and nutritional security and in mitigating climate change. The National Genebank (NGB) at ICAR-National Bureau of Plant Genetic Resources (NBPGR), New Delhi, acts as a repository of PGRs for future use. This study aimed at screening for the adventitious presence of transgenes in brinjal (Solanum melongena L.) accessions conserved in the NGB. The study targeted the collections made during 2007-2016 from areas adjacent to Bangladesh (Assam, Meghalaya, Mizoram, Tripura and West Bengal), where field trials of Bt brinjal event EE1 were conducted during 2005-2012 and commercial cultivation of this event was permitted in 2013.There could be an apprehension of both unintentional introgression and transboundary movement through borders. Adventitious presence of transgenes was checked in a set of 96 accessions of brinjal employing Polymerase Chain Reaction (PCR) and real-time PCR assays. As event EE1 carries cry1Ac gene for insect resistance with Cauliflower Mosaic Virus (CaMV) promoter (P-35S) and marker genes (nptII and aadA), so these genetic elements were targeted for qualitative GM testing. Based on the test results, transgenes were not detected in brinjal accessions conserved in NGB. Our study showed that brinjal and wild species collected from adjoining areas of Bangladesh, post field trials and release, do not contain the event EE1. The study presents an efficient and reliable method to ensure conservation of GM-free germplasm in the NGB.